Biomechanical study of medial meniscus after posterior horn injury: a finite element analysis. Issue 4 (11th March 2020) - Jiang, Peishi; Cui, Juncheng; Chen, Zhiwei; Dai, Zhu; Zhang, Yangchun; Yi, Guoliang
Abstract: We established an effective finite element model of knee joint for observation of stress and displacement of meniscus related changes after medial meniscus injury. Different types of medial meniscus injury can lead to varied meniscus stress and displacement changes. Stress and displacement concentration were found in fissure tip of meniscus tear compared to normal meniscus. The posterior horn injury of medial meniscus may initiate combined injury of medial meniscus posterior horn (MMPH) and that of medial meniscus body, and combined injury of MMPH and that of lateral meniscus anterior horn; fissure expansions regarding horizontal fissure, longitudinal fissure and grip-shaped fissure of MMPH were spotted.